Plasma cell free next-generation sequencing detects an unusual pneumonia pathogen in an immunocompetent adolescent with acute respiratory distress syndrome - Rodriguez, Katherine M.; Ramchandar, Nanda; Coufal, Nicole G. (Frontiers in Pediatrics, 2022)
This case details a rapid diagnosis of legionella pneumonia causing severe acute respiratory distress syndrome (ARDS) in an otherwise healthy adolescent through plasma microbial cell-free DNA next generation sequencing (mcfDNA-NGS). Diagnosis by mcfDNA-NGS of this unexpected pathogen led to narrowing of antimicrobials and the addition of glucocorticoids as adjunctive therapy for ARDS.